The effect of obesity on FibroScan parameters, cytokeratin-18, and fibroblast growth factor-21 levels - Keskin, Murat; Koca, Nizameddin (The European Research Journal, 2025)
Objectives: This study aimed to evaluate the differences in anthropometric, clinical, laboratory, and radiological parameters between obese and non-obese adolescents, focusing on the role of FibroScan parameters, Cytokeratin-18 (CK-18), and Fibroblast growth factor (FGF-21) in assessing metabolic and liver health. Methods: Anthropometric data were collected, and blood pressure was measured. Laboratory parameters, including fasting glucose, insulin, HOMA-IR, liver enzymes, lipids, CK-18, and FGF-21 levels, were assessed. Liver stiffness measurement (LSM) and controlled attenuation parameter (CAP) were measured using Fibroscan. Pearson’s correlation analyses were performed to identify associations between CK-18/FGF-21 levels and metabolic parameters. Results: A cross-sectional study involved 193 adolescents aged 10-18, including 87 obese and 106 non-obese participants. Obese adolescents had significantly higher fasting insulin, HOMA-IR, AST, ALT, GGT, uric acid, triglycerides, and LDL-cholesterol, with lower HDL-cholesterol levels (all P<0.001). CK-18 (P=0.05) and FGF-21 levels (P=0.002) were elevated in the obese group. CAP and LSM values were also significantly higher in obese participants (P<0.001). CK-18 and FGF-21 were positively correlated with fasting insulin, HOMA-IR, GGT, and triglycerides, indicating their potential as biomarkers for metabolic dysfunction. LSM correlated significantly with CK-18 (P=0.005) and FGF-21 (P=0.007). Conclusions: Obese adolescents exhibited significant metabolic and liver dysfunction. Elevated CK-18 and FGF-21 levels, along with abnormal FibroScan parameters, highlight the importance of these biomarkers in identifying early liver injury and metabolic abnormalities. These findings suggest that CK-18 and FGF-21 may be valuable non-invasive tools for assessing and managing obesity-related liver disease.